Method for rapid preparation of POSS hybrid materials using ionic liquid medium and its application
The rapid preparation of POSS hybrid materials through ionic liquid media solves the problems of low target content and complex matrix in sample preparation, realizes high-throughput enrichment detection of polypeptide antibiotics, and expands the application range of POSS hybrid materials.
Patent Information
- Application Number
- CN202410172617.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-02-07
AI Technical Summary
The prior art faces the problem of low content of target substances and complex matrix during sample preparation, and it is difficult to effectively extract and isolate polypeptide antibiotics, which limits its application in the field of IT-SPME.
POSS hybrid materials were prepared quickly by ionic liquid media, and good hydrophilicity and biocompatibility were prepared by introducing imidazole type 1-octyl-3-methylimidazole tetrafluoroborate as medium at high temperature for 8 minutes. POSS hybrid materials are used for the enrichment detection of hydrophilic compounds in polar environments.
The application range of POSS hybrid materials has been improved, and high-throughput enrichment detection of trace water-soluble polypeptide antibiotics in complex sample matrix is achieved, solving the problem of limited applicability of traditional materials in polar compound extraction.
Smart Images

Figure CN117986493B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibiotic enrichment detection, and in particular to a method for rapidly preparing a POSS hybrid material using an ionic liquid medium and an application thereof. Background Art
[0002] Peptide antibiotics (PTs) are a general term for antibiotics containing two or more amino acid structures, mainly including common cyclic glycopeptides (such as vancomycin, teicoplanin, etc.), lipopeptides (such as daptomycin, etc.) and other cyclic peptides, such as polymyxin B, colistin, bacitracin A, etc. Since these antibiotics have good antibacterial effects on many Gram-negative or Gram-positive bacteria, they have been widely used as veterinary drugs and feed additives in animal husbandry. At the same time, their abuse in feed may lead to drug residues in animal-derived foods, thereby threatening human health due to long-term consumption of foods containing drug residues. Since 1999, the European Union (EU) has banned bacitracin and virginiamycin from being used as growth promoters. The maximum residue limits of bacitracin, colistin and virginiamycin in animal-derived foods have been established in the range of 50 to 500 μg / kg. However, the analysis and detection of PTs in animal-derived foods is often limited by the low content of the target substances in the actual samples and the complex matrix. Therefore, it is of great significance to develop a sample preparation step to extract and separate the analytes from the complex matrix before instrumental analysis.
[0003] In the field of sample preparation, especially in-tube solid phase microextraction (IT-SPME), polymer monolithic materials have attracted great attention due to their advantages such as easy preparation, good permeability, fast mass transfer rate, easy surface modification and excellent pH stability. However, traditional organic polymer monolithic columns still have problems such as easy swelling, poor mechanical stability and low flux, which limit their application in the field of IT-SPME. To this end, the preparation of organic-inorganic hybrid monolithic columns by incorporating nanoparticles into polymers has become a mainstream way to improve material stability, provide higher adsorption specific surface area and thus enhance the enrichment performance of target substances. Polyhedral oligomeric silsesquioxane (POSS) is a nanoscale particle with a cage-like structure, which is often used as a functional monomer or cross-linking agent to significantly improve the surface mechanical properties of polymers (such as strength and stiffness), and improve the pH tolerance, antioxidant and temperature resistance of the material, thereby giving the material better adsorption performance. In particular, the hybrid monolithic column prepared by incorporating the POSS skeleton into an organic polymer has a continuous bed porous structure composed of through-pores and mesopores, which can provide more active sites. However, the strong hydrophobicity of the POSS skeleton usually limits its applicability in the extraction of polar compounds, so it is particularly important to introduce a reaction medium with good compatibility.
[0004] Ionic liquids (ILs) are salts in liquid state, usually composed of large organic cations and small inorganic / organic anions, with many excellent properties, such as low vapor pressure, high thermal stability and favorable solvation properties for polar and non-polar compounds. In the field of chromatography, ILs are also used as porogens to control the porosity and structural morphology of polymers, and are applied in the preparation of capillary microextraction adsorbents. As "designer solvents", slight changes in the cation or anion part of ILs will lead to changes in the initial rate and copolymerization kinetics, thereby preparing polymers with different physicochemical properties, and ultimately producing overall materials with various enrichment properties due to the different mass transfer characteristics of the polymers to meet diverse needs. Therefore, using ILs as a medium to solve the problem of poor solubility of hydrophobic nanomaterials, and based on this, developing a hybrid IT-SPME material with good hydrophilicity and biocompatibility, it has important practical value for the high-throughput enrichment detection of trace water-soluble PTs in complex sample matrices. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for quickly preparing a POSS hybrid material using an ionic liquid medium and an application thereof in view of the deficiencies of the above-mentioned prior art, introduce ILs as a porogen to solve the problem of poor solubility of a hydrophobic nano material POSS, and simultaneously adopt a zwitterionic monomer MPC with good biocompatibility as a main functional monomer and a rigid skeleton POSS-MA as a copolymerization monomer to enhance the mechanical stability of the overall column, and through a simple "one-pot" process, a POSS hybrid material with good hydrophilicity and biocompatibility is quickly prepared at high temperature using [C8mim][BF4] as a medium, the prepared POSS hybrid material has hydrophilicity and is used for the enrichment and detection of hydrophilic compounds in a polar environment, thereby improving the application range of the POSS hybrid material.
[0006] The present invention provides a method for rapidly preparing a POSS hybrid material using an ionic liquid medium, comprising the following steps:
[0007] S1, preparing a prepolymer solution of POSS hybrid material: taking MPC and POSS-MA as functional monomers, taking MBA as a cross-linking agent, adding the functional monomers and the cross-linking agent into a binary porogen composed of [C8mim][BF4] and DMF, after vortex mixing, adding AIBN as an initiator, and ultrasonically mixing to obtain a uniformly mixed prepolymer solution;
[0008] S2, rapid thermal polymerization reaction: the prepolymer solution prepared in S1 is introduced into the capillary, and then both ends of the capillary are sealed. After sufficient water bath polymerization reaction, a hydrophilic hybrid poly (MPC-co-POSS-co-MBA) monolithic column, i.e., POSS hybrid material, is obtained.
[0009] According to the method for quickly preparing POSS hybrid materials using ionic liquid media provided by the present invention, the mass ratio of MPC, POSS-MA, MBA, [C8mim][BF4], DMF and AIBN in S1 is 26.5 mg: 3.5 mg: 20.0 mg: 36.0 mg: 144.0 mg: 1.0 mg.
[0010] According to the method for rapidly preparing POSS hybrid materials using an ionic liquid medium provided by the present invention, the temperature of the water bath in S2 is 85° C., and the water bath time is 8 min.
[0011] According to the method for rapidly preparing POSS hybrid material using ionic liquid medium provided by the present invention, the post-treatment method of the POSS hybrid material in S2 is: after the reaction is completed, the capillary column is fully rinsed with methanol for 30 minutes, and the rinsed POSS hybrid material is evenly cut to a length of 3 cm, and stored for later use.
[0012] The present invention also provides an application of the POSS hybrid material, wherein the POSS hybrid material is used for enrichment and detection of hydrophilic compounds in a polar environment.
[0013] Compared with the prior art, the present invention has the following advantages:
[0014] The invention introduces ILs as a porogen to solve the problem of poor solubility of a hydrophobic nano material POSS, and simultaneously adopts a zwitterionic monomer MPC with good biocompatibility as a main functional monomer and a rigid skeleton POSS-MA as a copolymerization monomer to enhance the mechanical stability of the overall column. Through a simple "one-pot" process, imidazole-type 1-octyl-3-methylimidazolium tetrafluoroborate is used as a medium to prepare a POSS hybrid material with good hydrophilicity and biocompatibility at high temperature for 8 minutes. The material can be used for enrichment detection of hydrophilic compounds in a polar environment, thereby greatly improving the application range of the POSS hybrid material. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is the preparation flow chart of the POSS hybrid material prepared in Example 1;
[0016] Figure 2 is the CME-HPLC chromatogram of the PTs mixture;
[0017] Figure 3 is the SEM image of POSS hybrid material;
[0018] Figure 4 It is the Mapping spectrum of POSS hybrid material;
[0019] Figure 5It is a schematic diagram of water contact angle analysis of POSS hybrid materials;
[0020] Figure 6 Nitrogen adsorption-desorption isotherms and pore size distribution diagram of POSS hybrid materials;
[0021] Figure 7 It is the thermogravimetric analysis diagram of POSS hybrid material;
[0022] Figure 8 FTIR spectrum of POSS hybrid material. DETAILED DESCRIPTION
[0023] Example 1
[0024] This embodiment provides a method for rapidly preparing POSS hybrid materials using an ionic liquid medium, and the specific steps are as follows:
[0025] S1. Preparation of POSS hybrid material prepolymer solution: 26.5 mg of 2-methacryloyloxyethyl phosphorylcholine (MPC) and 3.5 mg of methacrylic isobutyl (POSS-MA) were weighed as functional monomers, 20.0 mg of N, N-methylenebisacrylamide (MBA) was weighed as a cross-linking agent, the functional monomer and the cross-linking agent were added to a binary porogen consisting of 36.0 mg of 1-octyl-3-methylimidazolium tetrafluoroborate ([C8mim][BF4]) and 144.0 mg of N, N-dimethylformamide (DMF), after vortex mixing, 1.0 mg of azobisisobutyronitrile (AIBN) was added as an initiator, and ultrasonic mixing was performed for 20 min to obtain a uniformly mixed prepolymer solution;
[0026] S2. Rapid thermal polymerization reaction: Introduce the prepolymer solution prepared in S1 into the capillary with a syringe, and then seal both ends of the capillary with rubber stoppers. Put the sealed capillary into a water bath at 85°C for polymerization reaction for 8 minutes to prepare a hydrophilic hybrid poly (MPC-co-POSS-co-MBA) monolithic column, i.e., POSS hybrid material.
[0027] Since the introduction of ILs, namely [C8mim][BF4], as a porogen can accelerate the rate of free radical polymerization, the preparation method provided in this embodiment can achieve rapid preparation.
[0028] This embodiment also provides a method for preparing a POSS hybrid material sample: after the polymerization reaction described in S2 is completed, the capillary column is fully rinsed with methanol for 30 minutes to remove residual monomers and other unreacted reagents, and the rinsed POSS hybrid material is evenly cut into a length of 3 cm and stored as a sample for later use.
[0029] This example provides a schematic diagram of the preparation process of using ILs porogen to quickly prepare POSS hybrid materials. Figure 1 shown.
[0030] As a good solvent for free radical polymerization reactions, ILs can induce the phase separation process of the polymer network, improve the thermal stability of POSS hybrid materials, and reduce the mass transfer resistance, thus meeting the enrichment requirements of water-soluble PTs in complex sample matrices.
[0031] The present invention introduces ILs as a porogen to solve the problem of poor solubility of hydrophobic nanomaterial POSS, and simultaneously adopts a zwitterionic monomer MPC with good biocompatibility as a main functional monomer and a rigid skeleton POSS-MA as a copolymerization monomer to enhance the mechanical stability of the overall column. Through a simple "one-pot" process, imidazole-type 1-octyl-3-methylimidazolium tetrafluoroborate is used as a medium to prepare a POSS hybrid material with good hydrophilicity and biocompatibility at high temperature for 8 minutes.
[0032] Example 2
[0033] This example provides a capillary microextraction (CME) experiment for detecting a target PTs mixed solution (a mixed solution of vancomycin, gramicidin and teicoplanin, which is a polypeptide antibiotic in a feed sample) using the POSS hybrid material prepared in Example 1. The specific steps are as follows:
[0034] S1, PTs mixed solution preparation: Weigh 1.00 mg of vancomycin, gramicidin and teicoplanin standards respectively and dissolve them in 1.0 mL of water. The stock solution concentration of the three standards is 1000 mg / L. Store in a refrigerator at -20°C away from light. Use the corresponding solvent to dilute to the required concentration when using.
[0035] S2. Activation of POSS hybrid material: The POSS hybrid material prepared in Example 1 was activated by passing methanol at a flow rate of 80.0 μL / min;
[0036] S3, PTs loading, washing and elution: 2 mL of PTs mixture was passed into the activated POSS hybrid material prepared in S2 at a flow rate of 80.0 μL / min. After all the PTs mixture was passed, the interfering matrix on the microextraction monolithic column was washed with 0.5 mL of 94% acetonitrile enrichment solution at a flow rate of 80.0 μL / min to fully load the polypeptide antibiotics. Finally, 20.0 μL of eluent was used to elute the PTs mixture analytes loaded on the microextraction monolithic column. The eluent was 40% ACN / 5 mmol / L triethylamine phosphate buffer with a pH value of 7.0. The flow rate of the eluent was 100.0 μL / min. After the eluent was recovered with a centrifuge tube, it was filtered with a 0.22 μm filter membrane to obtain a PTs mixed spiked sample for HPLC analysis.
[0037] For CME-HPLC analysis of peptide antibiotics in target feed samples:
[0038] The HPLC analysis was performed on a Shimadzu HPLC system equipped with two pumps (LC-20AD), an autosampler (SIL-20A), a diode array detector (SPD-M20A), and a column oven (CTO-20AC). The target peptides were separated and analyzed using an ACQUITY UPLC HSS T3 C18 column, 2.1 mm × 100 mm, 1.8 μm.
[0039] The elution of HPLC gradient consists of two mobile phases: phase A is an aqueous solution containing 0.1% formic acid; phase B is a methanol solution containing 0.1% formic acid; the specific procedure of gradient elution is as follows: gradient elution procedure: 0.0-0.5min, 5% phase B; 0.5-1.5min, 5%-15% phase B: 1.5-3.0min, 15%-90% phase B; 3.0-3.5min, 90% phase B; 3.6-5.0min, 5% phase B. Flow rate: 0.4mL / min; column temperature: 30℃; injection volume: 10μL.
[0040] CME-HPLC chromatogram Figure 2 As shown, curve a is the result of direct injection analysis of a mixed spiked sample of PTs with a concentration of 8000 μg / L without enrichment pretreatment; curve b represents the analysis and detection result of a mixed spiked sample of PTs with a concentration of 8 μg / L after being processed by the CME-HPLC-UV method;
[0041] In the figure, analyte label 1 is vancomycin, 2 is gramicidin, and 3 is teicoplanin.
[0042] The POSS hybrid material prepared in Example 1 can be used for the enrichment and detection of hydrophilic compounds in a polar environment, which greatly improves the application scope of the POSS hybrid material.
[0043] Example 3
[0044] The POSS hybrid material prepared in Example 1 was characterized.
[0045] First, prepare the standard solution of PTs: weigh 1.0 mg of PTs standard and dissolve it in 1.0 mL of water to prepare the standard solution of PTs. The standard solution of PTs can be stored in a refrigerator at -20°C away from light and diluted to the required concentration with the corresponding solvent when taking it.
[0046] ① The morphology of the POSS hybrid material was characterized by a field emission electron microscope (SEM) of model ZEISS Sigma 300 purchased from Germany. The magnification of the SEM was 500×, 1000×, 2000× and 10000×.
[0047] The characterization results are as follows Figure 3 As shown, the method magnifications of Figures a, b, c and d are 500×, 1000×, 2000× and 10000× respectively; Figure a shows that the prepared POSS hybrid material has a uniform polymer matrix and is well anchored on the inner wall of the capillary without cracking and wall detachment; Figure b shows that the prepared POSS hybrid material has a continuous porous overall matrix and a uniform internal network structure; Figures c and d show that the POSS hybrid material contains abundant 5μm through holes, i.e., large flow channels, which proves that the porous POSS hybrid material network structure is conducive to rapid mass transfer, thereby achieving the purpose of improving the extraction performance.
[0048] ② Energy dispersive X-ray spectroscopy characterization: Energy dispersive spectroscopy (EDS-Mapping) was used to characterize the composition of the POSS hybrid material.
[0049] The characterization results are as follows Figure 4 As shown, the distribution of S, N, O, Si, P, S and Cl elements can be clearly seen on the interface of the POSS hybrid material, further proving that the POSS hybrid material was successfully prepared.
[0050] ③ Characterization of water contact angle: 200 mg of POSS hybrid polymer material sample was pressed into a sheet with a thickness of about 1 mm, and the contact angle of water on the surface of the POSS hybrid material was characterized in situ using the hanging drop method. The characterization was performed using a contact angle measuring instrument purchased from Germany, Lauda Scientific.
[0051] The characterization results are as follows Figure 5As shown, it can be seen that the POSS hybrid material presents a lower water contact angle of 28.8°, which is attributed to the superhydrophilicity of the MPC-type zwitterions themselves and the successful modification of the strongly hydrophobic POSS skeleton.
[0052] ④ Characterization of specific surface area and pore size: The specific surface area and pore characteristics of the POSS hybrid material were characterized by a physical adsorption and desorption instrument model ASAP 2460 purchased from Micromeritics, USA. The POSS hybrid material sample was placed in a nitrogen atmosphere for degassing at a degassing temperature of 120°C and a degassing time of 500 min.
[0053] The characterization results are as follows Figure 6 As shown, a larger hysteresis loop was observed for the POSS hybrid polymer at higher relative pressures. Figure 5 The pore size analysis diagram of the POSS hybrid material is also included. From the figure, it can be seen that the POSS hybrid material prepared by ILs medium has more mesopores and through holes.
[0054] ⑤ Characterization by thermogravimetric analysis: The thermal stability of the POSS hybrid material was characterized by a synchronous thermal analyzer model STA449C / 6 / G purchased from PerkinElmer, USA. The POSS hybrid material sample was placed in a nitrogen atmosphere, and the temperature was increased from 30°C to 800°C at a rate of 10°C / min.
[0055] The characterization results are as follows Figure 7 As shown, the POSS hybrid material begins to decompose when the temperature reaches about 250°C and completely decomposes at about 600°C, indicating that the POSS hybrid material prepared in ILs medium has high thermal stability.
[0056] ⑥ Fourier transform infrared spectroscopy (FTIR) characterization: The characteristic groups of POSS hybrid materials were characterized by a Fourier transform infrared spectrometer purchased from Thermo Fisher Company, USA, model Thermo Nicolet 6700, with a wavelength range of 400-4000 cm -1 .
[0057] The characterization results are as follows Figure 8 As shown, POSS-MA has a wavelength of 1720 cm -1 and 1640cm -1 The stretching vibration peaks of can be attributed to the C=O and C=C double bonds of the methacrylate group, with a wavelength of 1090 cm -1 When the wavelength is 1250 cm -1 、1170cm -1 and 953cm -1The stretching vibration peaks at 1000 nm are attributed to P=O, PO-alkyl and N + The characteristic peaks of (CH3)3 can be observed on the POSS hybrid materials, which further proves the successful preparation of POSS hybrid materials.
[0058] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. An application of a POSS hybrid material rapidly prepared by an ionic liquid medium, characterized in that: The POSS hybrid material rapidly prepared by the ionic liquid medium is used for enrichment detection of hydrophilic compounds in polar environments; Wherein, the preparation method of the POSS hybrid material quickly prepared by the ionic liquid medium comprises the following steps: S1, preparing a prepolymer solution of POSS hybrid material: taking MPC and POSS-MA as functional monomers, taking MBA as a cross-linking agent, adding the functional monomers and the cross-linking agent into a binary porogen composed of [C8mim][BF4] and DMF, after vortex mixing, adding AIBN as an initiator, and fully mixing by ultrasound to obtain a uniformly mixed prepolymer solution; The mass ratio of MPC to POSS-MA is 26.5:3.5; S2, rapid thermal polymerization reaction: the prepolymer solution prepared in S1 is introduced into the capillary, and then both ends of the capillary are sealed. After the water bath polymerization reaction is sufficient, a hydrophilic hybrid poly (MPC-co-POSS-co-MBA) monolithic column, namely, a POSS hybrid material, is obtained.
2. The application of the POSS hybrid material rapidly prepared by the ionic liquid medium according to claim 1, characterized in that: The mass ratio of MPC, POSS-MA, MBA, [C8mim][BF4], DMF and AIBN described in S1 is 26.5:3.5:20.0:36.0:144.0:1.
0.
3. The application of the POSS hybrid material rapidly prepared by the ionic liquid medium according to claim 1, characterized in that, The temperature condition of the water bath in S2 is 85° C., and the water bath time is 8 min.
4. The application of the POSS hybrid material rapidly prepared by the ionic liquid medium according to claim 1, characterized in that, The post-treatment method of the POSS hybrid material in S2 is: after the reaction is completed, the capillary column is fully flushed with methanol for 30 minutes, and the flushed POSS hybrid material is evenly cut to a length of 3 cm and stored for later use.